An investigation of antifungal stewardship programmes in England. Issue 11 (November 2017) - Micallef, Christianne; Ashiru‐Oredope, Diane; Hansraj, Sejal; Denning, David W.; Agrawal, Samir G.; Manuel, Rohini J.; Schelenz, Silke; Guy, Rebecca; Muller‐Pebody, Berit; Patel, Rakhee; Howard, Philip; Hopkins, Susan; et al.
Abstract : Purpose. : We sought to explore the current status of antifungal stewardship (AFS) initiatives across National Health Service (NHS) Trusts within England, the challenges and barriers, as well as ways to improve current AFS programmes. Methodology. : An electronic survey was sent to all 155 acute NHS Trusts in England. A total of 47 Trusts, corresponding to 30% of English acute Trusts, responded to the the survey; 46 Trusts (98%) had an antimicrobial stewardship (AMS) programme but only 5 (11%) had a dedicated AFS programme. Overall, 20 (43%) Trusts said they included AFS as part of their AMS programmes. From those conducting AFS programmes, 7 (28%) have an AFS/management team, 16 (64%) monitor and report on antifungal usage, 5 (20%) have dedicated AFS ward rounds and 12 (48%) are directly involved in the management of invasive fungal infections. Results/Key findings. : Altogether, 13 acute Trusts (52%) started their AFS programme to manage costs, whilst 12 (48%) commenced the programme due to clinical need; 27 (73%) declared that they would increase their AFS initiatives if they could. Of those without an AFS programme, 14 (67%) responded that this was due to lack of resources/staff time. Overall, 12 Trusts (57%) responded that the availability of rapid diagnostics and clinical support would enable them to conduct AFS activities. Conclusion. : Although a minority of Trusts conduct dedicated AFS programmes, nearly half include AFS as part of routine AMS activities. Cost issues are the main driver for AFS, followed by clinical need. The availability of rapid diagnostics and clinical support could help increase AFS initiatives.